2017
DOI: 10.1097/bsd.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Posterior Cervical Foraminotomy

Abstract: Minimally invasive cervical foraminotomy is an effective procedure for decompression of cervical nerve roots regardless the type of the stenosis. Even employing minimally invasive technique still causes neck pain in the long term affecting up to 25% of patients. More randomized control studies are required to clarify the benefits of minimally invasive PCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Instability issues after partial facetectomy during PF may lead problems that require fusion, in general fusion after PF have rates of up to 5%. Recent retrospective studies of minimal invasive PF with over 1000 cases shown that a good level of decompression is achieved, i.e., to same or better NDI in comparison to ACDF [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
See 1 more Smart Citation
“…Instability issues after partial facetectomy during PF may lead problems that require fusion, in general fusion after PF have rates of up to 5%. Recent retrospective studies of minimal invasive PF with over 1000 cases shown that a good level of decompression is achieved, i.e., to same or better NDI in comparison to ACDF [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…The preserved motion may lead to restenosis as the degeneration continues with the risk of secondary surgery on the index level [34]. PF will lead to clinical success in 64-96% with a reoperation incidence of 4-7% in retrospective cohort studies [22][23][24][25][26][27][28][29][30][31][32][35][36][37].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…In the review done by Church et al [13] among 1,039 patients who underwent PCF, the total number of complications was 36; including 19 surgical site infections, 7 dural tears, 6 patients developed a new focal sensory disturbance, 3 patients had new focal weakness, and 1 scalp laceration from Mayfield head-holder placement. The PCF has also been associated with an increased risk of developing cervical kyphosis due to loss of facet joints integrity [11]. In contrast to this finding, in a biomechanical study on cervical stability following foraminotomy, Zdeblick et al [26] concluded that unilateral foraminotomy with preservation of more than 50% of the facet joint does not result in cervical alignment change.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it provides direct nerve root decompression with motion preservation of the involved segments [8,11−13]. Potential drawbacks compared with anterior procedures are the risk for postoperative kyphosis and higher risk for infection [11].…”
Section: Introductionmentioning
confidence: 99%
“…c showed right C4/5 uncal hypertrophy and disc protrusion which was decompressed in the same corresponding cut in d or radiological cervical instability, and associated myelopathy with anterior disc herniation and or calcification. Other relative contraindications are calcified disc and ossified posterior longitudinal ligaments [24,25].…”
Section: Discussionmentioning
confidence: 99%